Child with Down Syndrome in a peer group. - Jędrzejowska, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Agnieszka Jędrzejowska, Child with Down Syndrome in a peer group. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 351–372. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.16 The attitude towards people with disabilities has changed over the last century. Both deinstitutionalisation as well as integration and normalisation allowed many people with intellectual disabilities to improve their social situation. An example of such a systemic solution supporting the development of disabled persons are integration groups. The subject of this article is a report from a pilot study on the functioning of a group of children with Down syndrome within an integration group. The objective of this study was the presentation of the reasonability of inclusion within the integration group of children with Down’s Syndrome (with the homogeneous dysfunction). Observation and sociometric tests covered children with Down syndrome from two integration groups from kindergarten no. 109 in Wrocław, Poland. I consider the essence of integration, following A. Maciarz, to be the feeling of social bonds experienced by a disabled individual, a sense of belonging to a group, as well as the conviction that one is accepted by it, despite the fact that the standards adopted by their community are not always and not fully met by them. The research was carried out for six months in a kindergarten where I was a special educator.